A construção da identidade autista e neurodivergente: considerações teórico-críticas à luz da teoria psicanalítica - Silva, Távina Romão (2024)
Autism is a topic that generates divergences and a reason for dispute in several fields that intend to study it. Currently, it is possible to notice a very intriguing phenomenon: autism constituted as a question of identity, related to the perspective and the Movement for Neurodiversity. This perspective argues for the recognition of human brain diversity and positions autism as a brain difference. Furthermore, it advocates the existence of an “autistic and neurodivergent identity”. In this context, a study was carried out on the construction of identity of people who recognize themselves as autistic and understand themselves as neurodivergent. The research corpus was composed of first-person narratives, which were analyzed based on a theoretical-critical reflection supported by contributions from the psychoanalysis of Freud and Lacan. As specific objectives, we sought: a) investigate, based on the notion of identity and the concept of identification, in Freud and Lacan, how autistic identity is constituted; b) map, in the narratives, the decisive moments relating to recognizing oneself as autistic; c) analyze, through first-person narratives, how the “autistic identity” is articulated with the perspective of neurodiversity; d) reflect on how, based on the recognition of oneself as autistic and neurodivergent, narratives are constructed that give new meaning to people’s life stories and project a future based on “autistic identity”. To this end, initially, a historical review of autism was carried out, with a view to demarcating the transformations through which the topic has gone since the clinical description published by Leo Kanner to the current moment in which the emergence of the neurodiversity perspective is perceived. Then, a theoretical study was constructed on the concept of identification, the constitution of the Eu and the notion of identity based on psychoanalytic theory, considering, above all, Freudian, Lacanian and commentators’ indications on the subject. Furthermore, an analysis of first-person narratives was carried out, selected from three published works, with a view to tracing a path of understanding regarding the aforementioned identity construction. At these moments, psychoanalytic theory was a guide for the work carried out, considering its use as a critical social theory, interested in the subject’s entanglement with social and political phenomena. The analysis carried out based on the narratives reveals the strong presence of imaginary identifications, despite neurodiversity being produced discursively as an articulation of signifiers present in contemporary culture. In this way, this dissertation aimed to make use of psychoanalytic contributions, as far as it is appropriate, to outline research possibilities regarding the mentioned context, as well as to provide theoretical-critical reflections on the topic.